New insights into the spatial variability of microbial diversity and density in peatlands exposed to various electron acceptors with an emphasis on methanogenesis and CO2 fluxes - Shabbir, Sadaf; Qian, Chang; Faheem, Muhammad; Zhou, Fengwu; Yu, Zhi-Guo (Frontiers in Microbiology, 2024)
Peatlands play a crucial role in natural carbon cycling by affecting CH4 and CO2 emission. Yet, little is known about the specific interactions between external environmental factors and the microbial communities that produce greenhouse gases. Moreover, the amount of research conducted on terminal electron acceptors (TEAs) within peatland soils along vertical stratification gradients is also relatively limited. Therefore, a pilot-scale mesocosm study was conducted to evaluate the impact of 4 different TEAs i.e., SO42-; SO42- + humic acid (HA); HA, and Goethite, on CH4 and CO2 emission and microbial community structure along the depth. Briefly, SO42- addition increased CO2 production approximately twice (80-89.3%) compared to control, but it was slightly increased (18.18-24.7%) in SO42- + HA treatment. For Goethite and HA treatment, it also followed the same pattern as that of SO42- + HA. However, to a greater or lesser extent, all of these TEA treatments significantly inhibited the production of CH4. Community composition and network analysis showed that addition of TEAs primarily determines the composition of microbial communities, and microbial communities of each treatment differ in their taxa networks. Proteobacteria, Acidobacteria, Chloroflexi, and Bacteroidetes were the most abundant phyle in the mesocosms. The presence of methanotrophs i.e. Methylomirabilales, Methylococcales, and uncultured_methanogenic_archaeon explains the inhibition of CH4 emission in these mesocosms. A significant contribution made by this study is the advancement of our understanding of carbon (C) cycling (in terms of CH4 and CO2 emission) in microbe-rich environments exposed to TEAs. Future studies should focus on TAEs' long-term effects on microorganisms, enzymes, and therefore C storage in order to better understand the influences they have on the C cycling process.